High-field MR imaging in pediatric congenital heart disease: Initial results - Nguyen, Kim-Lien (Pediatr Radiol, 2014)
BACKGROUND: Comprehensive assessment of pediatric congenital heart disease (CHD) at any field strength mandates evaluation of both vascular and dynamic cardiac anatomy for which diagnostic quality contrast-enhanced magnetic resonance angiography (CEMRA) and cardiac cine are crucial. OBJECTIVE: To determine whether high-resolution (HR) CEMRA and steady-state free precession (SSFP) cine can be performed reliably at 3.0 T in children with CHD and to compare the image quality to similar techniques performed at 1.5 T. MATERIALS AND METHODS: Twenty-eight patients with a median age of 5 months and average weight 9.0 ± 7.8 kg with suspected or known CHD were evaluated at 3.0 T. SSFP cine (n = 86 series) and HR-CEMRA (n = 414 named vascular segments) were performed and images were scored for image quality and artifacts. The findings were compared to those of 28 patients with CHD of similar weight who were evaluated at 1.5 T. RESULTS: Overall image quality on HR-CEMRA was rated as excellent or good in 96% (397/414) of vascular segments at 3.0 T (k = 0.49) and in 94% (349/371) of vascular segments at 1.5 T (k = 0.36). Overall image quality of SSFP was rated excellent or good in 91% (78/86) of cine series at 3.0 T (k = 0.55) and in 81% (87/108) at 1.5 T (k = 0.47). Off-resonance artifact was common at both field strengths, varied over the cardiac cycle and was more prevalent at 3.0 T. At 3.0 T, off-resonance dark band artifact on SSFP cine was absent in 3% (3/86), mild in 69% (59/86), moderate in 27% (23/86) and severe in 1% (1/86) of images; at 1.5 T, dark band artifact was absent in 16% (17/108), mild in 69% (75/108), moderate in 12% (13/108) and severe in 3% (3/108) of cine images. The signal-to-noise ratio and contrast-to-noise ratio of both SSFP cine and HR-CEMRA images were significantly higher at 3.0 T than at 1.5 T (P < 0.001). CONCLUSION: Signal-to-noise ratio and contrast-to-noise ratio of high-resolution contrast-enhanced magnetic resonance angiography and SSFP cine were higher at 3.0 T than at 1.5 T. Artifacts on SSFP cine were cardiac phase specific and more prevalent at 3.0 T such that frequency-tuning was required in one-third of exams. In neonates, high spatial resolution CEMRA was highly reliable in defining extracardiac vascular anatomy.